Analisis Permainan Tradisional dalam Mengoptimalkan Kreativitas dan Berpikir Kritis Siswa SD Negeri 1 Bukit Tempurung Kabupaten Aceh Tamiang - Tengku Herlina Julia; Maisura Maisura; Rambang Muharramsyah (LPPM Institut Pendidikan Nusantara Global, 2026)
This qualitative descriptive study examines how traditional games enhance creativity and critical thinking among students at SD Negeri 1 Bukit Tempurung, Aceh Tamiang. Data were collected through observation, interviews, and documentation with teachers, students, and the principal, then analyzed using the Miles and Huberman model. Findings show that traditional games like engklek and congklak create active, collaborative, and enjoyable learning environments that develop critical thinking through decision-making and strategy formulation, while fostering creativity through idea generation and alternative problem-solving. Supporting factors include a conducive environment, teacher support, game simplicity, and student enthusiasm, though challenges such as limited time and game variation exist. The study confirms that traditional games effectively enhance creativity, critical thinking, and learning motivation in elementary students, serving as a valuable alternative instructional strategy.